1.
Solve for x.
3(2x − 1) + 7 = −44
Correct Answer
A. X = -8
Explanation
By distributing the 3 to both terms inside the parentheses, the equation becomes 6x - 3 + 7 = -44. Simplifying further, we get 6x + 4 = -44. Subtracting 4 from both sides gives 6x = -48. Finally, dividing both sides by 6, we find that x = -8.
2.
Solve for x.
6(2x − 5) = −(x + 4)
Correct Answer
A. X = 2
Explanation
By distributing the 6 to both terms inside the parentheses, we get 12x - 30. By distributing the negative sign to both terms inside the other parentheses, we get -x - 4. Combining like terms, we have 12x - 30 = -x - 4. By moving all the x terms to one side of the equation and the constant terms to the other side, we get 13x = 26. Dividing both sides by 13, we find that x = 2.
3.
Solve for y. That is, get the y variable by itself on one side of the equation.
2x + 5y = 10
Correct Answer
A.
Explanation
To solve for y, we need to isolate the y variable on one side of the equation. In this case, we can start by subtracting 2x from both sides of the equation. This gives us 5y = -2x + 10. Next, we divide both sides of the equation by 5 to solve for y. This gives us y = (-2/5)x + 2. Therefore, the correct answer is y = -2/5x + 2.
4.
Solve for x. That is, get the x variable by itself on one side of the equation.
3(x + 2) = y − 6
Correct Answer
A.
Explanation
To solve for x in the equation 3(x + 2) = y - 6, we need to isolate the x variable. We can start by distributing the 3 to both the x and 2 inside the parentheses, which gives us 3x + 6. The equation now becomes 3x + 6 = y - 6. To isolate the x variable, we can subtract 6 from both sides of the equation, resulting in 3x = y - 12. Finally, to solve for x, we divide both sides of the equation by 3, giving us the solution x = (y - 12)/3.
5.
Use the Equal Values Method to solve for the following systems of equations.
y = 7x − 5
y = −2x + 13
Correct Answer
A. X = 2 and y = 9
6.
Use the Equal Values Method to solve for the following systems of equations.
y = 3x − 1
y = 3x + 2
Correct Answer
A. No solution
Explanation
The given system of equations is y = 3x - 1 and y = 3x + 2. By comparing the coefficients of x in both equations, we can see that they are the same (3). However, the constant terms (-1 and 2) are different. This means that the lines represented by these equations have the same slope but different y-intercepts. Therefore, the lines are parallel and will never intersect, resulting in no solution.
7.
To rent a jet ski at Sam’s costs $25 plus $3 per hour. At Claire’s, it costs $5 plus $8 per hour.
Let x = the number of hours rented, and y = the total cost for the rentals.
Which two equations could be used to represent the cost the rent the jet skis at Sam's and Claire's?
(Select all that apply)
Correct Answer(s)
A. Y = 3x + 25
B. Y = 8x + 5
Explanation
The equation y = 3x + 25 represents the cost to rent a jet ski at Sam's, where $25 is the initial cost and $3 per hour is added. The equation y = 8x + 5 represents the cost to rent a jet ski at Claire's, where $5 is the initial cost and $8 per hour is added.
8.
To rent a jet ski at Sam’s costs $25 plus $3 per hour. At Claire’s, it costs $5 plus $8 per hour. At how many hours will the rental cost at both shops be equal?
Correct Answer(s)
4
4 hours
Explanation
The rental cost at Sam's is $25 plus $3 per hour, while at Claire's it is $5 plus $8 per hour. To find the number of hours at which the rental cost at both shops will be equal, we need to set up an equation. Let x be the number of hours. The equation will be: 25 + 3x = 5 + 8x. By solving this equation, we find that x = 4. Therefore, at 4 hours, the rental cost at both shops will be equal.
9.
Which colored line best represents the graph of the equation y = 4x + 3?
Correct Answer
A. Red
Explanation
The correct answer is Red because the equation y = 4x + 3 represents a linear function with a positive slope of 4. The red line is the only one that has a positive slope and is consistent with the equation given.
10.
Write the rule that can be best used to represent the table above (in y = mx+b form).
Correct Answer
y=2x-1
y = 2x - 1
y = 2x-1
Explanation
The given correct answer is y = 2x - 1. This equation represents a linear relationship between the variables x and y, where the coefficient of x is 2 and the constant term is -1. This means that for every increase of 1 in x, y will increase by 2. The equation is in the standard form of a linear equation, y = mx + b, where m represents the slope of the line and b represents the y-intercept. In this case, the slope is 2 and the y-intercept is -1.